Stroke‐related restless legs syndrome: Clinical and anatomo‐functional characterization of an emerging entity. (23rd December 2021) - Ruppert, Elisabeth; Hacquard, Aurélien; Tatu, Laurent; Namer, Izzie Jacques; Wolff, Valérie; Kremer, Stéphane; Lagha‐Boukbiza, Ouhaïd; Bataillard, Marc; Bourgin, Patrice
Abstract: Background and purpose: Stroke‐related restless legs syndrome (sRLS) secondary to ischemic lesions is an emerging entity and an interesting condition, but there are limited available data to help us further understand its underlying pathways. In this study, we characterized sRLS clinically, neuroanatomically and functionally. Methods: Consecutive patients hospitalized in the Stroke Unit of the University Hospital of Strasbourg were assessed clinically and electrophysiologically for sRLS characteristics. They underwent brain magnetic resonance imaging for the neuroanatomical study of involved structures, and received functional evaluations with 18 F‐FDG (2‐deoxy‐2‐[fluorine‐18]fluoro‐D‐glucose) positron emission tomography (PET) for glucose consumption, 123 I‐FP‐CIT ([123]I‐2beta‐carbometoxy‐3beta‐[4‐iodophenyl]‐N‐[3‐fluoropropyl]nortropane) single‐photon emission computed tomography for dopamine reuptake and PET with 18 F‐FDOPA ((3, 4‐dihydroxy‐6‐[18]F‐fluoro‐l‐phenylalanine) for presynaptic dopaminergic synthesis. Results: Sixteen patients with sRLS, eight women and eight men, aged 41–81 years, were included. The clinical characteristics of sRLS and idiopathic RLS were similar. Most patients presented with bilateral and symmetric de novo RLS. Eight patients had infarction in the lenticulostriate area (middle cerebral artery and internal carotid arteria). The body of the caudate nucleus was most commonly affected. Seven patients had sRLS secondary to ventral brainstem infarction (perforating branches of the basilar arteria) affecting the pons in six patients and the medulla oblongata in one patient. Both the corticospinal tract and the cortico‐pontocerebellar fibres were lesioned in all patients with brainstem stroke. One patient had infarction in the left posterior cerebellar vermis and occipital area (posterior cerebral artery and superior cerebellar artery). Isotopic explorations showed a significantly increased dopaminergic tone in the striatum ipsilateral to lenticulostriate infarction. Dopamine fixation was normal in patients with stroke outside of the lenticulostriate area. Conclusions: Clinicians should be aware of the characteristics of sRLS for the appropriate diagnosis and treatment of this condition. Abstract : Stroke‐related restless legs syndrome (sRLS) related to ischemic lesions is an emerging entity that we characterized clinically, neuroanatomically and functionally. The clinical characteristics of sRLS and idiopathic RLS were similar overall. Infarctions in sRLS patients most commonly affected the lenticulostriate area and the ventral brainstem. An increased dopaminergic tone in the striatum ipsilateral to lenticulostriate infarction was present. Both the corticospinal tract and the cortico‐pontocerebellar fibers were lesioned in RLS related to brainstem stroke. Clinicians should be aware of the characteristics of sRLS for the appropriate diagnosis and treatment of this condition.